Effects of beetroot juice intake on repeated performance of competitive swimmers - Moreno, Berta; Morencos, Esther; Vicente-Campos, Davinia; Muñoz, Alejandro; González-García, Jaime; Veiga, Santiago (Frontiers in Physiology, 2023)
Background: Beetroot juice is a sport supplement with a high level of evidence on the physical performance enhancement. However, in swimming, there is no clear data about the effects of beetroot juice on performance. Objective: To investigate whether an acute intake of beetroot juice (BJ) improves the performance of competitive swimmers in a repeated maximum swimming effort. Method: Thirteen national-level swimmers (6 females and 7 males), participated in this randomized, double-blind crossover study. In two different trials, swimmers ingested a 70-ml placebo shot (0.04 mmol NO3–; PLA) or a 70-ml Beet-It shot (6.4 mmol of NO3−beet juice [BJ]) 3 hours before undergoing a 6 × 100-m front-crawl maximal effort test with 7 minutes rest between each 100 m. Results: Overall, 100-m times showed no difference between the BJ and PLA groups (p = .364), although a possibly shorter time was observed for BJ in the last repetition (p = .104; mean difference [MD] = –0.99 s, mean-based inference [MBI] = 49/51/0). Participants in the BJ condition showed a possibly lower rate of perceived exertion in the first (p = .242, MD = –0.85, MBI = 70/28/2) and second repetitions (p = .165, MD = 1.15, MBI = 83/16/1), whereas Total Quality Recovery scale scores were likely higher in the first (p = .110, MD = 1.15, MBI = 83/16/1) and third (p = .082, MD = –0.77, MBI = 70/29/1) repetitions compared with those in the PLA group. Blood lactate concentration [La+] levels showed no differences between groups in any of the repetitions (p > .05, unclear), and we observed an increase in 100-m times for both BJ and PLA (BJ: p = .014, MD = –1.51 s; PLA: p = .029, MD = –1.57 s) after the fifth repetition. Conclusions: No clear differences in performance were observed in a 6 × 100-m repeated sprint test by competitive swimmers when supplementing (or not) with BJ. However, there was a trend toward a better recovery between efforts and a better tolerance of fatigue when swimmers ingested BJ.